Reliability and validity of the Turkish version of multidimensional quality of life scale - Cancer version 2 in patients with cancer - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2004)
This study examined the reliability and validity of the Turkish version of the Multidimensional Quality of Life Scale - Cancer Version 2 (MQOLS-CA2) in 72 people with cancer. The results indicated that the MQOLS-CA2 has good construct validity. Factor analysis confirmed the presence of 5 factors in the MQOLS-CA2: psychological well-being, physical well-being, nutrition, symptom distress, and interpersonal well-being. The correlation between the global scores of the MQOLS-CA2 and Medical Outcomes Study 36-Item Short Form Health Survey was significant (r = 0.78, P = .0001), supporting the criterion validity of the MQOLS-CA2. Results of the test-retest method showed that stability coefficients for the 5 subscales of the MQOLS-CA2 ranged from 0.56 (symptom distress) to 0.91 (general physical well-being). Cronbach alpha coefficients surpassed the 0.70 criterion for all subscales, indicating good internal consistency. The acceptability rate was excellent at 96% completed questionnaires. In conclusion, the findings suggest that the Turkish version of the MQOLS-CA2 is a valid and reliable instrument that can be used in cancer research.
Keywords: cancer patients; MQOLS-CA2; quality of life; SF-36; HEALTH SURVEY SF-36; QUESTIONNAIRE; VALIDATION; PROFILE